2021
DOI: 10.1021/acs.iecr.0c05214
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Enhancement of the Low-Temperature Selective Catalytic Reduction of NOx with NH3 by Bifunctional Catalytic Mixtures

Abstract: Enhancement of the low-temperature (LT) performance of selective catalytic reduction (SCR) of NOx with NH3 has been a spotlight in environmental catalysis. Here, we use a bifunctional catalytic system mixing V–W/Ti with an oxidative component, i.e., MnOx/CeO2, to achieve both improved LT-SCR activity and N2 selectivity. An integrated approach of steady-state kinetic measurements, chemical trapping techniques, time-resolved in situ FTIR spectroscopy, and density functional theory (DFT) calculations reveals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In our previous work, we found that improvement of SCR reactivity could be realized by utilizing the oxidizing properties of cobalt-cerium oxide (denoted as CoCeOx) catalyst and the acidity of the V2O5/TiO2. Moreover, we also revealed that oxidation ability was the dominant property to enhance the degradation performance for VOCs (Hu et al, 2021). Therefore, we propose a dual-layered structure to achieve an effective collocation with different functional areas, enhancing its total activity for NOx and VOCs removal.…”
Section: A C C E P T E D Mmentioning
confidence: 92%
“…In our previous work, we found that improvement of SCR reactivity could be realized by utilizing the oxidizing properties of cobalt-cerium oxide (denoted as CoCeOx) catalyst and the acidity of the V2O5/TiO2. Moreover, we also revealed that oxidation ability was the dominant property to enhance the degradation performance for VOCs (Hu et al, 2021). Therefore, we propose a dual-layered structure to achieve an effective collocation with different functional areas, enhancing its total activity for NOx and VOCs removal.…”
Section: A C C E P T E D Mmentioning
confidence: 92%
“…One of the possible applications of LDHs-derived materials is the selective catalytic reduction of nitrogen oxides with ammonia (NH 3 -SCR). The process aims to eliminate NO x produced by stationary and mobile sources of emissions to produce the mixture of N 2 and H 2 O [9]. In fact, the commercial catalysts of NH 3 -SCR, V 2 O 5 -MoO 3 (or WO 3 )-TiO 2 , exhibit relatively good catalytic activity; however, their performance is likewise limited, mainly due to a narrow temperature window, sensitivity to SO 2 and alkali metals, or the emission of cancerogenic vanadium [10].…”
Section: Introductionmentioning
confidence: 99%